Selenium-containing nanoparticles and bone related disorders: from synthesis, bone metabolism to disease therapy - Yue, Ziyang; Li, Haonan; Hu, Yi; Shen, Jinshen (Frontiers in Endocrinology, 2025)
Bone-related disorders (BRDs), such as osteoporosis, rheumatoid arthritis, and osteosarcoma, are major contributors to morbidity and disability worldwide. Conventional treatments are often limited by poor targeting, systemic toxicity, and insufficient long-term efficacy. Selenium (Se), an essential trace element, plays a pivotal role in maintaining redox homeostasis, immune balance, and bone remodeling. Selenium-containing nanoparticles (SeNPs) have emerged as promising platforms that integrate the biological activities of selenium with the tunable features of nanomaterials. This review provides a comprehensive overview of SeNPs, covering synthesis strategies, physicochemical properties, and their roles in regulating osteogenesis, osteoclastogenesis, oxidative stress, and inflammatory signaling in the skeletal microenvironment. We further highlight recent advances in applying SeNPs for the treatment of BRDs, including their incorporation into biomaterials and combination therapies such as photothermal and chemodynamic approaches. While preclinical studies show encouraging results, challenges remain in understanding long-term biosafety, biodistribution, and clinical translation. Overall, SeNPs-based nanomedicine offers significant potential for precision bone-targeted therapies and tissue regeneration.